Gendered pilgrimage: hajj and umrah from women’s perspectives - Thimm, Viola (Journal of contemporary religion, 2021)
Muslim women experience the pilgrimage to Mecca differently from their fellow males. This is not surprising when one considers the many feminist and gender-sensitive studies that have been dealing with social, political, historical, cultural, and economic issues from women’s and gendered perspectives. The surprising fact is the silence on the gendered experiences of Muslim pilgrimage—of hajj and umrah. This article examines fundamental differences in the experiences of female and male pilgrims related to their social relations, embodied experiences of the rituals, and socio-political positioning. The goal is to narrow the research gap regarding the Muslim pilgrimage–gender nexus on a descriptive level and to investigate contradictions between the normative approach of equality before God during pilgrimage and the lived, often oppressive, experiences of Muslim women on their pilgrimage journeys on a theoretical level.
Keywords: Geschlechterrolle; Frau; ʿUmra; Haddsch